Bulgarian consumers' objective understanding of front-of-package nutrition labels: a comparative, randomized study - Valentina A. Andreeva; Manon Egnell; Teodora Handjieva-Darlenska; Zenobia Talati; Mathilde Touvier; Pilar Galan; Serge Hercberg; Simone Pettigrew; Chantal Julia (BMC, 2020)
Abstract Background Bulgaria continues to lag behind other EU Member States with respect to chronic disease morbidity and mortality prevention. Methods In line with efforts targeting the improvement of dietary practices, this comparative study assessed objective understanding of five different front-of-package labels (FOPL) (Reference Intakes, Multiple Traffic Lights, Warning label, Nutri-Score, and Health Star Rating) in a sample of 1010 Bulgarian adults. Objective understanding was assessed by comparing the results of two nutritional quality ranking tasks (with and without FOPL) in an online randomized experiment featuring three food categories (pizza, cakes, breakfast cereals). Multivariable ordinal logistic regression models within and across food categories were fit. Results Compared with the Reference Intakes group, participants randomized to Nutri-Score exhibited the largest improvement in product ranking ability across food categories (OR = 2.33; 95% CI: 1.55-3.51), followed by those randomized to Health Star Rating (OR = 1.99; 95% CI: 1.32-3.00). Nutri-Score also performed best within two (pizza and breakfast cereals) of the three food categories. The Multiple Traffic Lights and Warning label groups did not display any significant improvement in objective understanding either within or across food categories compared with the Reference Intakes group. Conclusion Nutri-Score, which is a summary, interpretive, polychromatic FOPL, emerged as the most effective model in the Bulgarian context, with the potential to help consumers better understand the nutritional quality of food. The findings are of particular interest to public health policymakers in the region and across Europe, as the debate about an EU-wide FOPL model continues to gather momentum. Trial registration Registration number ACTRN12618001221246 . Trial registered at the Australian New Zealand Clinical Trials Registry.